2017
DOI: 10.1039/c7tb01803g
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of photo-electrochemical biosensors for ultrasensitive screening of mono-bioactive molecules: the effect of geometrical structures and crystal surfaces

Abstract: The controlled design of hierarchical CN-ST flowers is a key feature for creating biosensor surface electrodes for photo-electrochemical, ultrasensitive screening of mono-bioactive molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 68 publications
0
43
0
Order By: Relevance
“…Accordingly, these materials are widely applied in many important fields. Among them, nickel oxide (NiO) is an important semiconductor functional material [2], which is widely used in lithium ion batteries [3], electrocatalysis [4], thermal catalysis [5], gas sensor [6], electrochemistry [7,8], optical sensor [9] and biosensors [10][11][12][13][14] fields. Therefore, the preparation of various mesoporous NiO nanomaterials has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, these materials are widely applied in many important fields. Among them, nickel oxide (NiO) is an important semiconductor functional material [2], which is widely used in lithium ion batteries [3], electrocatalysis [4], thermal catalysis [5], gas sensor [6], electrochemistry [7,8], optical sensor [9] and biosensors [10][11][12][13][14] fields. Therefore, the preparation of various mesoporous NiO nanomaterials has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of simple and inexpensive analytical methods for selective and sensitive detection of DA is of particular interest. The electrochemical method is a great approach for DA sensing because of its short time delay production, high sensitivity and selectivity, easy handling, and applicability in vitro/in vivo, and an inexpensive analytical technique . Selective detection of DA in biological and physiological fluids is an important issue because of the low concentration of DA compared with other coexisting molecules such as ascorbic acid (AA) and uric acid (UA) .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the parent KIT-6, the slight decrements in N 2 adsorption capacity and pore size indicated that some pores of KIT-6 were still occupied by Co oxide NPs. 45 47 X-ray photoelectron spectroscopy (XPS) was used to determine the valence state of Co (Fig. S3 † ).…”
Section: Resultsmentioning
confidence: 99%